Evaluating the Public Climate School, a multi-component school-based program to promote climate awareness and action in students: A cluster-controlled pilot study - Jan Keller; Michael Eichinger; Myriam Bechtoldt; Shuyan Liu; Michael Neuber; Felix Peter; Carina Pohle; Gerhard Reese; Fabian Schäfer; Stephan Heinzel (Elsevier, 2024)
Introduction: Despite the potential of school-based programs targeting climate awareness and action to support students in addressing the climate crisis and to improve their mental health and well-being, there is limited evidence for their effectiveness. In preparation for a cluster-randomized controlled trial, we assessed the feasibility of evaluating the Public Climate School (PCS), a one-week school program in Germany, and its effects on theory-based behavioral and psychological outcomes. Material and methods: We enrolled 158 students from 11 classes (grades 7-13) into a cluster-controlled pilot study. Four classes were allocated to the waitlist control group and 7 to the intervention group participating in the PCS in November 2021. Using online surveys, we assessed theory-based behavioral and psychological outcomes at baseline and follow-up. Two-level models were used to investigate changes in outcomes. Results: 125 students completed the baseline and follow-up survey (dropout rate: 21 %). For most outcomes we observed no between-group differences, except for pro-environmental communication and engagement (e.g., posting on social media; p=.040) and perceptions of environmental norms (p=.001) in the anticipated direction. Conclusion: This study confirmed the feasibility of evaluating the PCS and provides parameter estimates to guide sample size calculations and study design decisions for future research. Together with recent work on the association between collective action and mental health, the effect of the PCS on pro-environmental communication and engagement highlights the value of examining effects of education for sustainable development programs on student health and linking them to collective action in future work.